Quality and productivity improvement through industrial engineering tools - 439493 Lau, Kam Fatt (Skudai : Universiti Teknologi Malaysia, 2001)
Project Paper (Bachelor of Engineering (Mechanical)) - Universiti Teknologi Malaysia, 2001